2007
DOI: 10.1037/0022-006x.75.5.752
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate models of men's and women's partner aggression.

Abstract: This exploratory study was designed to address how multiple factors drawn from varying focal models and ecological levels of influence might operate relative to each other to predict partner aggression, using data from 453 representatively sampled couples. The resulting cross-validated models predicted approximately 50% of the variance in men's and women's partner aggression. The 3 strongest direct predictors of partner aggression for men and women were dominance/jealousy, marital adjustment, and partner respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(217 citation statements)
references
References 73 publications
14
191
3
9
Order By: Relevance
“…Findings on gender differences in psychological aggression are less conclusive with both males and females reporting high levels of psychological aggression (Jose and O'Leary, 2009). Finally, in general, men experience more cognitive jealousy in relationships than do women (Aylor & Dainton, 2001) and jealousy is a strong predictor of partner aggression for men and women (O'Leary, Smith Slep, O'Leary, 2007). Nevertheless, previous research has not examined how these variables differ in unilaterally vs. bilaterally violent therapy-seeking couples.…”
Section: Jealousy Psychological Aggression and Relationship Satisfacmentioning
confidence: 64%
“…Findings on gender differences in psychological aggression are less conclusive with both males and females reporting high levels of psychological aggression (Jose and O'Leary, 2009). Finally, in general, men experience more cognitive jealousy in relationships than do women (Aylor & Dainton, 2001) and jealousy is a strong predictor of partner aggression for men and women (O'Leary, Smith Slep, O'Leary, 2007). Nevertheless, previous research has not examined how these variables differ in unilaterally vs. bilaterally violent therapy-seeking couples.…”
Section: Jealousy Psychological Aggression and Relationship Satisfacmentioning
confidence: 64%
“…Although existing models do not suggest systematic differences in risk factors for men and women in IPA perpetration (e.g., O'Leary et al, 2007;Riggs & O'Leary, 1996;White et al, 2001), general aggression literature has suggested some differences among genders in levels of perpetration (e.g., Exum, 2006). Therefore, potential gender effects were explored by examining main and interactive effects of gender in each model.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is depicted by facilitators' views about the initiation and motivations of DV. Research about partner violence risk factors (e.g., Godbout, Dutton, Lussier, & Sabourin, 2009;Medeiros & Straus, 2006;O'Leary, Smith Slep, & O'Leary, 2007) confirms that violence in the family of origin is an influential risk factor of DV perpetration as well as other individual and dyadic factors (e.g., anger expression, insecure attachment, marital adjustment) more closely related to partner abuse perpetration than the aforementioned factors examined in the intervention protocols. It is therefore suggested that a more comprehensive evidence-based empirical assessment of the associated motivations of partner abuse is required to determine salient factors of DV.…”
Section: Facilitator Background and Program Structurementioning
confidence: 99%